Effect of grain size, texture and density of precipitates on the hardness and tensile yield stress of Mg-14Gd-0.5Zr alloys. (15th January 2017) - Li, Rongguang; Xin, Renlong; Liu, Qing; Chapuis, Adrien; Liu, Shifeng; Fu, Guangyan; Zong, Lin
Abstract: In this study, an age-hardenable Mg–14Gd–0.5Zr (wt.%) alloy was used as a model material to investigate the effects of grain size, texture and density of precipitates on the hardness and 0.2% proof tensile yield stress. Six kinds of samples with different grain size, texture and density of precipitates were prepared by varying the extrusion process and aging treatment. The microstructure and texture of the samples were examined by electron backscatter diffraction and transmission electron microscope. The examination results indicate that 0.2% proof yield stress of the Mg-Gd alloys were largely affected by the grain size and texture, while the hardness of the alloys was predominately controlled by the density of precipitates. This study reveals that the grain size, texture and density of precipitate can have much different influences on the hardness and 0.2% proof yield stress for the Mg-Gd alloys. It raises an important issue about the mechanical-testing standards and product-design guidelines for the age-hardenable magnesium alloys. Graphical abstract: Highlights: Grain size, texture and precipitates have much different influences on hardness and proof stress for Mg-Gd alloys. The 0.2% proof stress of the alloys was largely affected by grain size and texture. The hardness of the alloys was predominately controlled by the density of precipitates.